Pengaruh Kualitas Pelayanan Terhadap Kepuasan Wisatawan Pada Bus Arofah Trans: The Influence of Service Quality on Tourist Satisfaction on Arofah Trans Buses - Muhammad Heykal; Marvelichi Aulia Asshiddiiqi; Ellen Aurellie Basuki (OGZ Research & Publishing, 2025)
Purpose: This study aims to analyze the effect of service quality on tourist satisfaction among users of Arofah Trans Bus services and to identify the service dimensions that contribute most to enhancing satisfaction. Methodology: A quantitative approach with a causal research design was employed. The sample consisted of 36 respondents selected through purposive sampling. The research instrument was an online questionnaire using a five-point Likert scale. Data were analyzed using simple linear regression. Findings: The results indicate that service quality has a positive and significant effect on tourist satisfaction, with a regression coefficient of 1.320 and a significance value of 0.000 (<0.05). The coefficient of determination (R²) of 0.990 shows that 99% of the variation in satisfaction is explained by service quality.